Learning Your Way into a Life of Crime (Fiction): Assessing Sisters-in-Crime as a Unique Learning Organization - Patricia A. Gouthro (Adult Education Research Conference, 2007)
Sisters in Crime (SinC) is explored as a unique learning organization dedicated to addressing discrimination against women mystery writers, and to promoting the writing of women in the area of crime fiction.